(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s ((3eMeO Hf eMeO MSjf GdNhGfSGQjs)
(3ChdgG (B:s
(3Gdbhd aj GdCOdI GdYbdjI hGdbhGYO GdCUhdjI GdTQYjI hGdahGFO(B...s
(3BNQgG (B:s
(3hdcf dh bjd HLhGR GdGYJeGO Ydi GdXfhf GdJj LQJ GdYGOI Ydi GYJHGQgG aj eYQaI ePgH GdZjQ(B...(3dCfgG dh de Jcf eYJHQI dfHg GdTQY Ydjg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B543s
(3GdPQjYI(B:(3L(B21(3,U(B194(3,Qbe(B5173s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs